Youth Political Participation in The Digital Age: Preparing A New Society of Good and Smart Digital Citizens - Prima Roza; Epin Saepudin; Gregorius Prasetyo Adhitama (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The aim of this research is to investigate the youth political participation in the digital public sphere and to understand their efficacy. The political participation of the younger generation is very important for the development of democracy in Indonesia given their significant numbers. The color of future democracy in this regard, is largely determined by their involvement in carrying out their roles as the pillar of democracy. This research used the method of survey to look at the trending themes for political engagement of university students in social media. This study revealed that the young generation involvement in political participation can take many different forms, including participating in social activities, fundraising, having talks about current events, reacting to government actions, etc. It also found that they prefer using Instagram and Twitter over other social media to express their political goals. The younger generation has shown good efficacy in political participation. However, skills in the use of citizenship technology are also a much-needed requirement to generate political participation in the era of digital age, that brings virtues to democracy